Fiscal Implications of the 18th Amendment : The Outlook for Provincial Finances - Pasha, Aisha Ghaus (World Bank, Washington, DC, 2014)
Following the transition to democracy in 2008, two very important political developments took place. These were the announcement of the 7th National Finance Commission Award, which was agreed upon in December 2009 in Lahore, Pakistan, and the unanimous ratification by Parliament of the 18th Amendment to the Constitution in April 2010. Both developments have the potential of fundamentally restructuring the way Pakistan is governed in the future. This paper is divided into four sections. The first provides a quick overview of the 18th Amendment and Its Major Fiscal Implications on Provincial Governments, including new functional responsibilities and institutions and financing of new responsibilities. The 18th Amendment brought important institutional changes and the fiscal powers of the provinces have been enhanced. As a result, the 18th Amendment will lead to a more balanced and decentralized structure of government of Pakistan and to an enhanced empowerment by the provinces. The second section provides an outlook for provincial finances and trends in fiscal variables and discusses borrowing and debt levels and ways to raise provincial resources. Under the 18th Amendment, the provinces now have greater access to domestic or foreign borrowing, but this has to be carefully monitored. The third section focuses on the potential for a new revenue sharing system and fiscal rules, including revenue sharing arrangements and exploring fiscal rules for provincial governments. The final section identifies a potentially large set of pending emerging issues. These are related to: devolution of particular functions; the distribution of assets/liabilities and flow of income; implications of the joint and equal ownership of natural resources by federal and provincial governments; impact of the 18th Amendment on the planning process; the future role of local governments; and the overall implications of decentralization on growth.